Narrow‐leafed lupin (Lupinus angustifolius L.) β‐conglutin: A multifunctional family of proteins with roles in plant defence, human health benefits, and potential uses as functional food - Jose C. Jimenez‐Lopez (Legume Science, 2020)
Abstract Lupinus angustifolius or narrow‐leafed lupin (NLL) is an important Pulse world‐wide and an outstanding alternative source of high quality proteins. NLL β‐conglutin (vicilin or 7S acid globulin), a multigene family of proteins, is the main representative protein in NLL seeds exhibiting multifunctional properties and benefits recently discovered. These functions may result from specific structural features of NLL β‐conglutins in comparison with most legume vicilin proteins. From the agricultural side, NLL β‐conglutin proteins (1a) exert antifungal properties promoting enhanced plant resistance to necrotrophic oomycete pathogens and (1b) displaying functional interplay between storage protein mobilization and seed oxidative metabolism as a functional regulatory and signalling crossroad for the control of physiological underlying processes of the seed dormancy breakage and release, during germination, and seedling growth. NLL β‐conglutins benefits go beyond nutritional properties because displayed nutraceutical functions make them an outstanding source of innovative ingredients for functional food. They have antioxidant activity and anti‐inflammatory properties, which are able to improve inflammatory‐related diseases such as type 2 diabetes through (a) regulation of insulin signalling pathway, (b) improving insulin sensitivity, (c) facilitating glucose uptake by cells, (d) together with their capacity for balancing the oxidative homeostasis, metabolic, and signalling pathways (e) while reducing reactive oxygen specie production and increase cellular oxidative defence capacity. Interestingly, NLL β‐conglutins also display anti‐nutritional properties as proteins capable to elicit allergic responses in sensitized individuals. This review outlines newly discovered knowledge of the narrow‐leafed lupin β‐conglutin proteins drawing on information gained from structure‐functional properties, agriculture benefits, as well as nutraceutics and molecular allergy point of views.